KORELASI KETERAMPILAN MEMBACA PEMAHAMAN DENGAN KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 20 PADANG - Ayuni, Qurrata; Tressyalina, Tressyalina (Universitas Negeri Padang, 2019)
ABSTRACTÂ The purpose of this research was to describe things as follows. First, it describes the skills of reading comprehension grade VII JUNIOR 20 Country field. Second, it describes the writing skills text description grade VII JUNIOR 20 Country field. Third, explain the relationship between the keterampilaan reading comprehension with writing skills text description grade VII JUNIOR 20 Country field. Type of this research is quantitative research with the method korelasional. The research design used was the korelasional relationship of two variables. The population of this research grade VII SMP Negeri Padang 20 listed in the teaching of 2018/2019 with a total of 254 students scattered in seven classes. The sample in this study amounted to 48 people. Sample taken using a simple random technique with a precision of 15% using a proportional random sampling techniques. Research instrument this is a test performance, namely, test write text description and objective tests the skills of reading comprehension text description. Based on the results of the study it was concluded that research done about the relationship skills reading comprehension dengana writing skills text descriptions have a relationship on a level may 95% i.e. thitung is greater than ttabel with dk = n-1. Thus, it can be noted that the higher the reading comprehension skills of students will be increasingly higher skill levels write a text description of the students.Â Kata Kunci: Korelasi, Membaca Pemahaman, Menulis, Teks Deskripsi